ANALYSIS OF THE INFLUENCE OF HUMAN CAPITAL ON ECONOMIC GROWTH IN REGENCIES/CITIES IN EAST KALIMANTAN PROVINCE - Gabriel Leo Nardo Ginting Manik; I Nyoman Mahaendra Yasa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Indonesia is an archipelagic country comprising several large islands, including Kalimantan. Kalimantan is one of the largest islands in the world and has been selected as the location for the development of the new capital city, Ibu Kota Nusantara (IKN). The goal of economic development is to achieve higher and more equitable economic growth across all regions. However, economic growth disparities remain in East Kalimantan, particularly among the 10 regencies/cities within the province. Key determinants of economic growth include life expectancy, average years of schooling, and the open unemployment rate. This research is classified as associative research using a quantitative approach. The data source consists of secondary data obtained from the Central Statistics Agency (BPS) to construct panel data for regencies/cities in East Kalimantan Province from 2018 to 2023, covering 10 regencies/cities. The study comprises 60 observations in total. Data analysis techniques include descriptive statistical analysis and panel data regression analysis. The results of the study show: Life expectancy, education level, and open unemployment rate have a significant simultaneous effect on economic growth in regencies/cities in East Kalimantan Province. Life expectancy has a positive but not significant effect on economic growth, education level has a positive and significant effect on economic growth, and the open unemployment rate has a negative and significant effect on economic growth. The government can prioritize improving the qualifications of the workforce through training and education programs aligned with local labor market needs, strengthening economic infrastructure to enhance regional accessibility and competitiveness, optimizing the utilization of local resources in regencies/cities across East Kalimantan, and allocating resources and attention to economic factors that directly influence economic growth in the region.